2014
DOI: 10.1097/pec.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prescription Opioid Use in Pediatric Emergency Department Patients

Abstract: Opioid use for pain-related pediatric ED visits has increased significantly from 2001 to 2010, particularly among adolescents. Emergency department providers must be vigilant in balancing pain relief with minimizing the adverse effects of opioid analgesics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 32 publications
(45 reference statements)
5
71
1
Order By: Relevance
“…The available evidence concerning the benefits and harms of long-term opioid therapy in children and adolescents is limited, and few opioid medications provide information on the label regarding safety and effectiveness in pediatric patients. However, observational research shows significant increases in opioid prescriptions for pediatric populations from 2001 to 2010 (36), and a large proportion of adolescents are commonly prescribed opioid pain medications for conditions such as headache and sports injuries (e.g., in one study, 50% of adolescents presenting with headache received a prescription for an opioid pain medication [37,38]). Adolescents who misuse opioid pain medication often misuse medications from their own previous prescriptions (39), with an estimated 20% of adolescents with currently prescribed opioid medications reporting using them intentionally to get high or increase the effects of alcohol or other drugs (40).…”
Section: Scope and Audiencementioning
confidence: 99%
“…The available evidence concerning the benefits and harms of long-term opioid therapy in children and adolescents is limited, and few opioid medications provide information on the label regarding safety and effectiveness in pediatric patients. However, observational research shows significant increases in opioid prescriptions for pediatric populations from 2001 to 2010 (36), and a large proportion of adolescents are commonly prescribed opioid pain medications for conditions such as headache and sports injuries (e.g., in one study, 50% of adolescents presenting with headache received a prescription for an opioid pain medication [37,38]). Adolescents who misuse opioid pain medication often misuse medications from their own previous prescriptions (39), with an estimated 20% of adolescents with currently prescribed opioid medications reporting using them intentionally to get high or increase the effects of alcohol or other drugs (40).…”
Section: Scope and Audiencementioning
confidence: 99%
“…In 2012, there were as many opioid prescriptions written (259 million) as there were adults in the US (Paulozzi, Mack, & Hockenberry, 2014). Prescriptions for opioids have increased significantly in adult (Mazer-Amirshahi, Mullins, Rasooly, van den Anker, & Pines, 2014) and pediatric emergency departments (Mazer-Amirshahi, Mullins, Rasooly, van den Anker, & Pines, 2014), and ambulatory settings (Olfson, Wang, Iza, Crystal, & Blanco, 2013). A study of trends in prescription medication use and abuse among college students found evidence for significant increases in prescriptions for stimulants and decreases in opioid prescriptions among college students from 2003-2013; during that time, rates of stimulant abuse increased, while rates of opioid abuse decreased (McCabe, West, Teter, & Boyd, 2014).…”
Section: Epidemiology Of Prescription Drug Abusementioning
confidence: 99%
“…In addition to adverse drug-drug reactions due to polypharmacy, it makes it increasingly difficult for patients to correctly manage these prescriptions, which may lead to unintentional poisonings. There has also been a rapid rise of opioid prescription rates in all age groups and rates of illicit drug use are higher in this age group as opposed to adults older than 65 years [21][22][23][24]. This may have contributed to the increase in visits for this demographic as some studies have found the majority of unintentional ingestions involve analgesics, particularly opioids [25,26].…”
Section: Discussionmentioning
confidence: 99%